A new method to evaluate the residual activity in patients undergoing 131I thyroid therapy. Issue 8 (December 2015) - Ostinelli, A.; Duchini, M.; Conti, V.; Bonfanti, P.; Rossi, S.; Cacciatori, M.
Highlights: The radioiodine administration is a therapeutic approach to hyperthyroidism. This procedure estimates the 131 I activity in patients undergoing thyroid therapies. A suitable detector was chosen and its response vs activity was characterized. The method significantly reduces the error margins within a range of ± 11%. The reliability of the method is confirmed by experimental data. Abstract: The radioiodine administration is a standard therapeutic approach to both benign thyroid diseases, such as hyperthyroidism, and carcinomas. The high administered 131 I activities are of radiation protection concern, due to relevant patient residual contamination. The aim of this work was to develop a new procedure based on external radiometric surveys and on a mathematical model in order to estimate the 131 I activity in patients undergoing hyperthyroidism radioiodine therapy. In the first stage of this study, a suitable detector was chosen and its response vs. activity was characterized. The experimental verification was performed measuring the ambient dose equivalent rate from patients receiving radioiodine administration. The results confirm the reliability of the proposed method, as shown by the slight differences between the administered activities and the ones calculated from external measurements. Furthermore, the same procedure was applied to detect the percentage residual activity in patients at two preset time intervals: 4 hours and 4 days after the radioiodine administration. The obtained results clearly highlight that the method can ensure a level of reliability compatible with the radiation protection purposes.